Association between time of residence and self-perception of distress, interpersonal relationships, and social role in Venezuelan immigrants in Lima, Peru 2018–19: mixed-methods study - Delgado-Cáceres, Frank Milton (2022)
Background: Immigrants arriving in a new country face changes that affect their social, employment, and migratory status. We carried out a mixed-methods study in the rapidly growing Venezuelan immigrant population in Lima, Peru. The objective was to determine whether there was an association between time in Peru and self-perception of symptom distress (SD), interpersonal relationships (IR), and social role (SR). Methods: The quantitative central component consisted of a cross-sectional study, surveying 152 participants using the Outcome Questionnaire 45.2 (OQ-45.2). The qualitative component, based on phenomenology, explored experiences and challenges during the migration process. Semi-structured in-depth interviews were conducted in 16 informants. Results: An association that was observed was the increase in the risk of clinically significant SR score with additional years of age. All informants mentioned having witnessed or experienced xenophobia in Peru. Every informant stated that significant labor differences existed between the countries. The most reported somatic symptoms were symptoms of anxiety and alterations of sleep. Additionally, no informant expressed a desire to remain in Peru long term. Conclusions: A minority of participants registered a clinically significant total score and in each of the three domains of SD, IR, and SR. No association between months in Lima and the self-perception of distress was found. However, this could be due to the short amount of time spent in Peru and any change in self-perception might only be perceived after years or decades spent in Peru. This study is one of the first to use mixed-methods to explore the mental health of the immigrant Venezuelan population.